Managing Peaceful Transitions : Evidence and Experience - Cliffe, Sarah (World Bank, Washington, DC, 2012)
How can recent Bank-led research on development, security and conflict inform policy choices in Middle East and North Africa (MENA)? The Arab spring has presented a level of protest and political transition in the region not seen since the fall of the Ottoman Empire and the end of the colonization period in the middle of the twentieth century. However, research shows that leadership changes in MENA have often been followed for a couple of years by the heightened risk of conflict and violence as newly-arrived regimes and citizenries attempt to assert their authority and rights. This quick Note considers that question from the perspective of the 2011 World Development Report (WDR) on 'conflict, security, and development' and a complementary regional Bank study.